2010
DOI: 10.1007/s10637-010-9450-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic induction by simvastatin in human lung cancer A549 cells via Akt signaling dependent down-regulation of survivin

Abstract: Statins, HMG-CoA reductase inhibitors have been studied for their antiproliferative and proapototic effects. Recently, statin-induced apoptosis has been associated with down-regulation of survivin expression in cancer cells. However, the mechanism of deregulated survivin by simvastatin on lung cancer is still unclear. Herein, we demonstrated that simvastatin induced caspase-dependent apoptosis in A549 lung cancer cells. Simvastatin also resulted in a decrease in the expression of phosphorylated Akt. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Benefi cial effects Adverse effects Breast cancer [12][13][14][15] 18% reduction in incidence with hydrophobic statin use (P = 0.02) Use of hydrophobic statins associated with a fourfold increased risk of progesterone receptor-negative breast cancer 37% reduction in estrogen receptor/progesterone receptornegative cancer (P = 0.02) Low-grade and less-invasive tumor burden 33% decreased cancer recurrence after conventional treatment (P = 0.02) Colon cancer [16][17][18][19][20][21][22][23][24] Approximately 10% reduction in the risk of colorectal carcinoma 39% increased risk of newly detected adenomas in patients taking statins for at least 3 years (P = 0.024) 49% reduction in adenomatous polyp recurrence 3-5 years post initial polypectomy (P < 0.01) 54% increased risk of new colorectal adenomas in type two diabetics prescribed statins for 3 years who had a prior history of colorectal adenomas (P = 0.007) Smaller number of polyps (P = 0.002) and polyp size (P = 0.03) Lower incidence of advanced polyps (P = 0.03) Synergestic effects with conventional chemotherapeutic agents Prostate cancer [25][26][27][28][61][62][63] 8% reduced risk of prostate cancer 55% increased risk in total prostate cancer with everuse of statins in men aged 50 years or older Signifi cant reduction in high-grade or high-volume disease Improved freedom from biochemical failure (P < 0.001) and salvage therapy (P = 0.001) Improved relapse-free survival (P < 0.001) 69% reduction in intratumoral infl ammation (P = 0.047) Hepatocellular cancer [29][30][31] 8-month (P = 0.003) to 9-month (P = 0.006) longer survival when statin added to transarterial embolization therapy ± chemotherapy 37% reduction in hepatocellular cancer among diabetics Hematologic cancers [32-35, 86,87] 39% decreased incidence of lymphomas Increased osteoclast activity in multiple myeloma patients treated with statins 55% improved event-free survival in follicular lymphoma (P = 0.001) Greater than two-fold increase in statin use among patients with lymphoma or multiple myeloma compared with patients with orthopedic (P = 0.009) or otorhinolaryngolic (P = 0.001) malignancies 60% decreased risk of multiple myeloma Reduced resistance drug-refractory multiple myeloma Miscellaneous [36]…”
Section: Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…Benefi cial effects Adverse effects Breast cancer [12][13][14][15] 18% reduction in incidence with hydrophobic statin use (P = 0.02) Use of hydrophobic statins associated with a fourfold increased risk of progesterone receptor-negative breast cancer 37% reduction in estrogen receptor/progesterone receptornegative cancer (P = 0.02) Low-grade and less-invasive tumor burden 33% decreased cancer recurrence after conventional treatment (P = 0.02) Colon cancer [16][17][18][19][20][21][22][23][24] Approximately 10% reduction in the risk of colorectal carcinoma 39% increased risk of newly detected adenomas in patients taking statins for at least 3 years (P = 0.024) 49% reduction in adenomatous polyp recurrence 3-5 years post initial polypectomy (P < 0.01) 54% increased risk of new colorectal adenomas in type two diabetics prescribed statins for 3 years who had a prior history of colorectal adenomas (P = 0.007) Smaller number of polyps (P = 0.002) and polyp size (P = 0.03) Lower incidence of advanced polyps (P = 0.03) Synergestic effects with conventional chemotherapeutic agents Prostate cancer [25][26][27][28][61][62][63] 8% reduced risk of prostate cancer 55% increased risk in total prostate cancer with everuse of statins in men aged 50 years or older Signifi cant reduction in high-grade or high-volume disease Improved freedom from biochemical failure (P < 0.001) and salvage therapy (P = 0.001) Improved relapse-free survival (P < 0.001) 69% reduction in intratumoral infl ammation (P = 0.047) Hepatocellular cancer [29][30][31] 8-month (P = 0.003) to 9-month (P = 0.006) longer survival when statin added to transarterial embolization therapy ± chemotherapy 37% reduction in hepatocellular cancer among diabetics Hematologic cancers [32-35, 86,87] 39% decreased incidence of lymphomas Increased osteoclast activity in multiple myeloma patients treated with statins 55% improved event-free survival in follicular lymphoma (P = 0.001) Greater than two-fold increase in statin use among patients with lymphoma or multiple myeloma compared with patients with orthopedic (P = 0.009) or otorhinolaryngolic (P = 0.001) malignancies 60% decreased risk of multiple myeloma Reduced resistance drug-refractory multiple myeloma Miscellaneous [36]…”
Section: Malignancymentioning
confidence: 99%
“…Additionally, statins may sensitize lung cancer cells to the effects of chemotherapy and ionizing radiation by impairing various growth factors and inducing the apoptosis of cancer cells via the inhibition of the Akt pathway, which plays a major role in tumor cell proliferation, survival and invasiveness. [65][66]28] Other in vitro studies have shown that statins modulate the activity of tumor suppressors, proinflammatory proteases and cell cycle regulatory proteins, inhibiting the formation of lung cancer cells. [67][68][69] Clinical data regarding the use of statins as anti-tumor or therapeutic agents in lung cancer is limited.…”
Section: Lung Cancermentioning
confidence: 99%
“…However, the results showed that they are not effective. Thus, effective diagnosis and identification of effective molecular therapeutic agents are required to treat lung cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of simvastatin used in the present study was lower and the exposure time is particularly much shorter compared with that used in most of in vitro cancer cells (Campbell et al, 2006;Hwang et al, 2010). Up to 25 M, simvastatin did not produce any toxic effect on MLTC-1 cells (Data not shown).…”
Section: Discussionmentioning
confidence: 68%